High-damage-tolerance and high-fatigue-resistance nickel-based high-temperature alloy and manufacturing method, alloy product and application thereof

By optimizing the elemental composition and manufacturing process, the volume fraction and uniformity of the γ' phase are improved, which solves the problem of insufficient damage tolerance and fatigue resistance of traditional nickel-based superalloys under high temperature and high stress conditions, and achieves a significant improvement in the high temperature stability and fatigue resistance of high damage tolerance and high fatigue resistance nickel-based superalloys.

CN121496237APending Publication Date: 2026-02-10NINGBO ZHONGKE XIANGLONG LIGHTWEIGHT TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511754276.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Traditional high-damage-tolerance, high-fatigue-resistance nickel-based superalloys suffer from insufficient damage tolerance, limited fatigue resistance, and insufficient high-temperature stability under high-temperature, high-stress, and complex cyclic loading environments. In particular, they are prone to defects and uneven distribution of γ' strengthening phase during additive manufacturing, making it difficult to meet the requirements for long-term high-temperature service.

Method used

By optimizing elemental composition and manufacturing process, the volume fraction and uniformity of the γ' phase are improved. Combined with grain boundary strengthening and defect suppression, alloy powder is prepared by rotating electrode process and formed into a high-damage-tolerance, high-fatigue-resistant nickel-based superalloy through additive manufacturing, ensuring the stability and uniform distribution of the γ' phase in the alloy.

Benefits of technology

It significantly improves the damage tolerance, fatigue resistance and high temperature stability of the alloy, and the fatigue life is increased to 650℃/1150MPa without fracture. It maintains excellent performance at high temperature, and the tensile strength and elongation are outstanding at high temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121496237A_ABST
    Figure CN121496237A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-based high-temperature alloy with high damage tolerance and high fatigue resistance and a manufacturing method, an alloy product and application thereof. The nickel-based high-temperature alloy comprises 8.0%-12.5% of Cr, 12.0%-16.5% of Co, 2.0%-4.0% of W, 3.0%-6.0% of Mo, 3.0%-6.0% of Al, 2.0%-4.0% of Ti, 2.0%-4.5% of Nb, 0.05%-2.0% of Hf, 0.05%-0.10% of C, 0.005%-0.015% of B, 0.1%-1.0% of Fe, 0.2%-1.0% of V, less than or equal to 0.005% of Sc, less than or equal to 0.05% of La, less than or equal to 0.05% of Mg, less than or equal to 0.02% of Ce, less than or equal to 3.0% of Re, less than or equal to The balance is Ni and inevitable impurities; the multiple technical barriers of high-volume-fraction gamma'phase stability control, grain boundary-precipitated phase synergistic strengthening, additive manufacturing defect suppression and the like are broken through, and the damage tolerance, the anti-fatigue performance and the high-temperature stability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nickel-based superalloy technology, specifically to a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, its manufacturing method, alloy products, and applications. Background Technology

[0002] Nickel-based superalloys are key materials in aerospace, energy, and high-end equipment industries, and their performance directly determines the service life and reliability of hot-end components such as engine turbine disks and blades. Traditional high-damage-tolerance, high-fatigue-resistance nickel-based superalloys often face the following technical bottlenecks under high-temperature, high-stress, and complex cyclic loading environments: Insufficient damage tolerance: Conventional alloys are prone to local stress concentration under high temperature fatigue conditions, which leads to premature initiation of stationary slip bands and crack initiation. Insufficient grain boundary strength also easily causes crack propagation along grains, thus limiting the damage tolerance performance of the material.

[0003] Limited fatigue resistance: During additive manufacturing, defects such as component segregation, porosity and lack of fusion are easily generated, which become the origin of fatigue cracks; at the same time, the volume fraction of the γ' strengthening phase is low (usually less than 40%) and unevenly distributed, making it difficult to effectively disperse cyclic loads, resulting in fatigue life that is difficult to exceed the 10^4 cycles level.

[0004] Insufficient high-temperature stability: In high-temperature environments above 900℃, the γ' strengthening phase of traditional alloys is prone to coarsening or dissolution, and the interdiffusion between the anti-oxidation coating and the substrate is intensified, resulting in a sharp drop in strength and mid-temperature brittleness, making it difficult to meet the requirements of long-term high-temperature service.

[0005] Currently, although some alloys have improved their oxidation resistance and solid solution strengthening effect by adjusting the content of elements such as Cr, Co, and W, they have not yet broken through multiple technical barriers such as "high volume fraction γ' phase stability control", "grain boundary-precipitate synergistic strengthening" and "additive manufacturing defect suppression".

[0006] The above background information is disclosed only to assist in understanding the inventive concept and technical solution of this invention. It does not necessarily belong to the prior art of this patent application, nor does it necessarily provide technical teachings. In the absence of clear evidence, the novelty and inventiveness of the above application shall be deemed to be incomplete. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention proposes a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, its manufacturing method, alloy products, and applications. It overcomes multiple technical barriers, including "high volume fraction γ' phase stability control," "grain boundary-precipitate synergistic strengthening," and "additive manufacturing defect suppression," thereby improving damage tolerance, fatigue resistance, and high-temperature stability.

[0008] To achieve the above objectives, the technical solution of the present invention is as follows: On one hand, this invention provides a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, comprising: Cr: 8.0%-12.5%, Co: 12.0%-16.5%, W: 2.0%-4.0%, Mo: 3.0%-6.0%, Al: 3.0%-6.0%, Ti: 2.0%-4.0%, Nb: 2.0%-4.5%, Hf: 0.05%-2.0%, C: 0.05%-0.10%, B: 0.005%- 0.015%, Fe: 0.1%-1.0%, V: 0.2%-1.0%, Sc: ≤0.005%, La: ≤0.05%, Mg: ≤0.05%, Ce: ≤0.02%, Re: ≤3.0%, Ru: ≤3.0%, Ta: ≤5.0%, S: ≤0.01%, P: ≤0.015%, Si: ≤0.2%, Mn: ≤0.40%, Pb: ≤0.1%; balance Ni and unavoidable impurities.

[0009] This invention proposes a high damage tolerance and high fatigue resistance nickel-based superalloy, its manufacturing method, alloy products, and applications. It breaks through multiple technical barriers such as "high volume fraction γ' phase stability control", "grain boundary-precipitate synergistic strengthening" and "additive manufacturing defect suppression", and improves damage tolerance, fatigue resistance and high temperature stability.

[0010] As a preferred technical solution, the total content of Al and Ti elements is 5.0%-10.0%, and the weight ratio of Al to Ti elements is (0.75-2.0):1.

[0011] As a preferred technical solution, the alloy contains a γ' strengthening phase with a volume fraction of ≥50%.

[0012] On the other hand, the present invention provides a method for manufacturing a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, to obtain a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy part as described in any of the preceding claims, comprising the step of preparing alloy powder using a rotating electrode process, the process comprising: Provide alloy electrode rods that meet chemical composition requirements; In a protective atmosphere and vacuum environment, the electrode rod is rotated at high speed and its end is heated to a molten state to form a liquid film; The liquid film is broken up by the action of centrifugal force and the pressure of a protective atmosphere to form metal droplets, which then solidify to form alloy powder. Collect alloy powder of the desired particle size.

[0013] As a preferred technical solution, the chemical composition of the alloy electrode rod includes: a metallic element with a purity of ≥99.9%.

[0014] As a preferred technical solution, the chemical composition of the alloy electrode rod includes Al and Ti elements, and the Al and Ti elements are added in the form of Al-Ni and Ti-Ni master alloys during the preparation of the alloy electrode rod.

[0015] As a preferred technical solution, the electrode rod rotates at a speed ≥15000 r / min to generate centrifugal force, the pressure of the protective atmosphere is 0.35-0.55 MPa, and the vacuum degree of the vacuum environment is ≤1×10⁻⁶. -3 Pa.

[0016] As a preferred technical solution, prior to the rotating electrode process, the alloy electrode rod is prepared by vacuum melting, including the following steps: Vacuum up to ≤5×10 -3 Pa, under a protective gas atmosphere, is heated to 1500-1700℃ and held for 25-35 minutes, during which time it is stirred until the composition is uniform to obtain molten metal; Molten metal is poured into a mold to form a casting; After cooling to room temperature, the casting is machined to remove the oxide layer on its surface, so that the surface roughness Ra≤1.6μm.

[0017] In another aspect, the present invention provides an alloy article made of a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy as described in any of the preceding claims or an alloy powder manufactured by the method described in any of the preceding claims.

[0018] Furthermore, this invention provides an application of the alloy article as described above, wherein the high damage tolerance, high fatigue resistance nickel-based superalloy or the alloy powder is formed into a metal article by additive manufacturing process 3D printing, and the application fields of the metal article include at least one of the following: Aerospace field: Used in the manufacture of key hot-end components such as high-pressure turbine blades, combustion chamber flame tubes, and turbine disks for aero-engines, enabling integrated forming of internal cooling channels for blades; Energy and power sector: Used in high-temperature turbine blades for gas turbines, heating surface components for waste heat boilers, and high-temperature structural components for the primary loop of nuclear reactors; High-end equipment sector: Used in automotive turbocharger rotors, high-temperature furnace rollers in industrial furnaces, and internal components of high-temperature reaction vessels in the chemical industry.

[0019] This invention provides a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, its manufacturing method, alloy products, and applications, which have the following beneficial effects: 1) The present invention provides a high damage tolerance and high fatigue resistance nickel-based superalloy, its manufacturing method, alloy products and applications, which breaks through multiple technical barriers such as "high volume fraction γ' phase stability control", "grain boundary-precipitate phase synergistic strengthening" and "additive manufacturing defect suppression", and improves damage tolerance, fatigue resistance and high temperature stability.

[0020] 2) This invention provides a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, its manufacturing method, alloy products, and applications, combining solid solution strengthening and... Phase precipitation strengthening; using Al and Ti as... The main phase-forming elements are controlled by increasing the total content of (Al+Ti) and precisely adjusting the (Al and Ti) ratio (1.5-2.0:1) to ensure that a volume fraction of over 50% of the phase is uniformly dispersed in the alloy. The strengthening phase provides the core for room temperature and high temperature precipitation strengthening of the alloy; Co, as the main solid solution strengthening element, can effectively improve the tensile strength and creep resistance of the alloy, and increase... The phase content is increased and its dissolution temperature is improved; Cr element (8.0%-12.5%) ensures high-temperature oxidation resistance and corrosion resistance above 900℃, forming a dense Cr2O3 oxide film; Nb, Ta and Hf are mainly soluble in Choosing it can effectively improve Phase content, inhibition Phase growth and dissolution, changes The phase composition enhances the antiphase domain boundary energy, while the small amounts of Nb and Ta dissolved in the matrix effectively reduce the matrix stacking fault energy, thereby improving the matrix's instantaneous tensile strength, creep resistance, and thermal fatigue performance. W, Mo, and V, as strong solid solution strengthening elements, synergistically strengthen the alloy with the high volume fraction γ' phase, further enhancing its room temperature and high temperature strength. C and B elements optimize grain boundary properties, while La, Ce, and Mg elements purify grain boundaries and inhibit grain boundary sliding. Hf element modifies grain boundary carbides and... The morphology of the precipitated phase produces curved grain boundaries, thereby delaying crack initiation and propagation, effectively promoting alloy toughness and improving alloy damage tolerance. Actual measurements show that the high damage tolerance and high fatigue resistance nickel-based superalloy provided in this application has a fatigue life of 650℃ / 1150MPa, 2*104^cyc, without fracture. Its high damage tolerance stems from the synergistic effect of "fine grain structure + grain boundary strengthening + ultra-high volume fraction γ' phase dispersion": the fine grain structure promotes the uniform distribution of dislocations and slip systems, inhibits the initiation of stationary slip bands and crack initiation, while numerous grain boundaries effectively hinder the propagation and connection of primary cracks, delaying the formation time of the main crack during service; the uniform dispersion of 50%-60% volume fraction γ' nano-precipitates hinders dislocation slip during crack initiation and primary crack propagation, stimulates the simultaneous activation of multiple slip systems, promotes uniform dislocation distribution, and effectively inhibits crack nucleation and the propagation of stationary slip bands; simultaneously, Nanoscale precipitates form a "high-density barrier wall" along the crack propagation path, forcing the crack to continuously change direction and bypass the precipitates, significantly increasing crack propagation resistance and delaying the formation time of the main crack. Under high-temperature conditions, the high content of Al, Ti, B, and C elements, as well as the introduction of Hf, promotes… The precipitation of phases and carbides at grain boundaries pins the grain boundaries, causing straight grain boundaries to bend and hindering crack initiation and extension at the grain boundaries. The high content of Cr and Al elements effectively enhances the alloy's oxidation resistance at high temperatures and alleviates mid-temperature brittleness caused by oxidation corrosion. At the same time, La, Ce, and Mg elements deeply purify the grain boundaries, reduce the segregation of harmful elements such as P and S, improve the grain boundary bonding strength, prevent crack extension along grain boundaries, and improve damage tolerance. The high fatigue resistance of the high-damage-tolerance, high-fatigue-resistance nickel-based superalloy provided in this application is mainly achieved through "defect control + high-stability microstructure": First, defect source control, with precise composition design reducing the risk of cracking during additive manufacturing from the perspective of solidification and melting mechanisms. Simultaneously, rotating electrode powdering reduces powder inclusions and hollow powder, and precise SLM forming process effectively avoids the formation of various defects, thus inhibiting the initiation of fatigue cracks from the source; Second, high volume fraction γ' phase fatigue-resistant design, with 50%-60% of the γ' phase uniformly dispersed... The high-efficiency dislocation dispersion under cyclic loading avoids local dislocation accumulation and stress concentration. Simultaneously, the fine-grained structure and high volume fraction γ' work synergistically to induce fatigue crack initiation within the grains and extend the initiation period by more than 30%. Thirdly, grain boundary strengthening is enhanced; boron and zirconium elements improve the grain boundary resistance to fatigue cracking, and the high volume fraction γ' pinning effect on the grain boundaries results in a creep rupture performance of ≥100h at 750℃ with a stress of 650MPa and a fatigue life of 650℃ / 1150MPa, 2*10⁴ cyc, thus improving fatigue resistance. The core of the high-damage-tolerance, high-fatigue-resistance nickel-based superalloy provided in this application, which maintains excellent performance at temperatures of 900℃ and above, lies in "ultra-high volume fraction γ' phase high-temperature stability + oxidation corrosion resistance + solid solution strengthening": the synergistic optimization of multiple elements such as Al, Ti, Co, and Nb increases the γ' phase content and high-temperature stability, making the γ' phase content exceed 50% and raising the dissolution temperature to 1180℃. This ensures that at 927℃, there is still a uniformly dispersed γ' nano-strengthening phase of more than 50 vol%, continuously providing high-temperature strengthening; rapid solidification via SLM reduces dendrite spacing, suppresses dendrite segregation, and weakens the effect of poorly soluble and difficult-to-diff elements such as Ta, Nb, Hf, W, and Re on the composition uniformity. The effects of homogeneity and topologically close-packed (TCP) precipitation ensure the uniform distribution of solid solution and precipitation strengthening elements after homogenization heat treatment, guaranteeing the full utilization of solid solution strengthening and precipitation strengthening effects. Cr forms a dense Cr2O3 oxide film at high temperatures, with a film thickness stable at 2-5 μm, effectively preventing corrosive elements such as O and S from penetrating the alloy interior and suppressing mid-temperature brittleness. Refractory elements such as W, Mo, Ta, Nb, and Hf dissolve in the γ matrix and γ' nano-strengthening phase, enhancing the high-temperature strength of the matrix while slowing down the atomic diffusion rate at high temperatures, further suppressing γ' phase coarsening, ensuring that the alloy's tensile strength at 927℃ remains above 700 MPa and its elongation is ≥10%, thus improving high-temperature stability. Attached Figure Description

[0021] Figure 1 The equilibrium solidification phase diagram of the alloy product provided in Example 1; Figure 2 The morphology of the γ' precipitate phase and the density scanning electron microscope (SEM) morphology of the alloy product provided in Example 1; Figure 3 Solidification cracking index of the alloy product provided in Example 1 - Phase volume fraction comparison chart (red pentagrams indicate the properties of this alloy). Detailed Implementation

[0022] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0023] This invention provides a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, comprising: Cr: 8.0%-12.5%, Co: 12.0%-16.5%, W: 2.0%-4.0%, Mo: 3.0%-6.0%, Al: 3.0%-6.0%, Ti: 2.0%-4.0%, Nb: 2.0%-4.5%, Hf: 0.05%-2.0%, C: 0.05%-0.10%, and B: 0.005%-0.10%. 0.15%, Fe: 0.1%-1.0%, V: 0.2%-1.0%, Sc: ≤0.005%, La: ≤0.05%, Mg: ≤0.05%, Ce: ≤0.02%, Re: ≤3.0%, Ru: ≤3.0%, Ta: ≤5.0%, S: ≤0.01%, P: ≤0.015%, Si: ≤0.2%, Mn: ≤0.40%, Pb: ≤0.1%; balance Ni and unavoidable impurities.

[0024] This invention proposes a high damage tolerance and high fatigue resistance nickel-based superalloy, its manufacturing method, alloy products, and applications. It breaks through multiple technical barriers such as "high volume fraction γ' phase stability control", "grain boundary-precipitate synergistic strengthening" and "additive manufacturing defect suppression", and improves damage tolerance, fatigue resistance and high temperature stability.

[0025] Preferably, the total content of Al and Ti elements is 5.0%-10.0%, and the weight ratio of Al to Ti elements is (0.75-2.0):1.

[0026] Preferably, the alloy contains ≥50% by volume of a γ' strengthening phase.

[0027] On the other hand, the present invention provides a method for manufacturing a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, to obtain a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy part as described in any of the preceding claims, comprising the step of preparing alloy powder using a rotating electrode process, the process comprising: Provide alloy electrode rods that meet chemical composition requirements; In a protective atmosphere and vacuum environment, the electrode rod is rotated at high speed and its end is heated to a molten state to form a liquid film; The liquid film is broken up by the action of centrifugal force and the pressure of a protective atmosphere to form metal droplets, which then solidify to form alloy powder. Collect alloy powder of the desired particle size.

[0028] Preferably, the chemical composition of the alloy electrode rod includes: elemental metals with a purity of ≥99.9%.

[0029] Preferably, the chemical composition of the alloy electrode rod includes Al and Ti elements, and the Al and Ti elements are added in the form of Al-Ni and Ti-Ni master alloys during the preparation of the alloy electrode rod.

[0030] Preferably, the electrode rod rotates at a speed ≥15000 r / min to generate centrifugal force, the pressure of the protective atmosphere is 0.35-0.55 MPa, and the vacuum degree of the vacuum environment is ≤1×10⁻⁶. -3 Pa.

[0031] Preferably, prior to the rotating electrode process, the alloy electrode rod is prepared by vacuum melting, comprising the following steps: Vacuum up to ≤5×10 -3 Pa, under a protective gas atmosphere, is heated to 1500-1700℃ and held for 25-35 minutes, during which time it is stirred until the composition is uniform to obtain molten metal; Molten metal is poured into a mold to form a casting; After cooling to room temperature, the casting is machined to remove the oxide layer on its surface, so that the surface roughness Ra≤1.6μm.

[0032] In another aspect, the present invention provides an alloy article made of a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy as described in any of the preceding claims or an alloy powder manufactured by the method described in any of the preceding claims.

[0033] Furthermore, this invention provides an application of the alloy article as described above, wherein the high damage tolerance, high fatigue resistance nickel-based superalloy or the alloy powder is used to form metal articles by additive manufacturing process metal 3D printing, and the application fields of the metal article include at least one of the following: Aerospace field: Used in the manufacture of key hot-end components such as high-pressure turbine blades, combustion chamber flame tubes, and turbine disks for aero-engines, enabling integrated forming of internal cooling channels for blades; Energy and power sector: Used in high-temperature turbine blades for gas turbines, heating surface components for waste heat boilers, and high-temperature structural components for the primary loop of nuclear reactors; High-end equipment sector: Used in automotive turbocharger rotors, high-temperature furnace rollers for industrial furnaces, and internal components of high-temperature reaction vessels in the chemical industry.

[0034] Example 1 This invention provides a method for preparing alloy products, comprising the following steps: S101 prepares the alloy electrode rod by vacuum melting, including the following steps: The raw materials are prepared according to the following percentages by weight (total mass 10kg): Cr: 10.5%, Co: 14.5%, W: 3%, Mo: 4.5%, Al: 4.5%, Ti: 3%, Nb: 3.5%, Hf: 1%, C: 0.08%, B: 0.01%, Fe: 0.5%, V: 0.6%, Sc: 0.003%, La: 0.02%, Mg: 0.04%, Ce: 0.01%, Re: 2.0%, Ru: 2.0%, Ta: 3.0%; the balance being Ni and unavoidable impurities. After pretreatment, the raw materials are loaded into a vacuum induction melting furnace and evacuated to a vacuum of 3×10⁻⁶. -3³ Pa is heated to 1650℃ under an Ar protective gas atmosphere and held at that temperature for 30 minutes, stirring until the composition is uniform to obtain molten metal. The molten metal is then cast into a mold with a diameter of 70mm and a length of 400mm. After cooling to room temperature, a 70mm × 400mm electrode rod is obtained. The 70mm × 400mm electrode rod is then machined to remove the surface oxide layer, ensuring a surface roughness Ra = 1.2μm. In the preparation of the alloy electrode rod, the Al and Ti elements are added in the form of Al-Ni and Ti-Ni master alloys. S102 includes the step of preparing alloy powder using a rotating electrode process, the process comprising: After installing the electrode rod obtained in step S101, adjust the coaxiality to 0.08 mm and set the vacuum degree of the atomization chamber to 8 × 10⁻⁶. -4 The atmosphere is filled with Ar to a protective pressure of 0.45 MPa. The electrode rod is rotated at a high speed of 23,500 r / min to generate centrifugal force. The electrode rod is then heated at high speed and its tip is atomized by an 11 kW plasma arc for 35 minutes to form a liquid film. The liquid film is broken up by the centrifugal force and the pressure of the protective atmosphere to form metal droplets. The metal droplets solidify to form alloy powder. The alloy powder is sieved to 15-53 μm, has a sphericity of 97%, and a bulk density of 4.705 g / cm³. 3 The hollow pasta content was 0.3%; The present invention provides an alloy article made from alloy powder manufactured by the method described above.

[0035] Furthermore, the present invention provides an application of the alloy article as described above, wherein the high damage tolerance, high fatigue resistance nickel-based superalloy or the alloy powder is formed into a metal article by additive manufacturing process metal 3D printing, comprising the following steps: Selective laser melting forming: In a protective atmosphere within a forming chamber, a selective laser melting process is used to melt and form high-damage-tolerance, high-fatigue-resistance nickel-based superalloy powder layer by layer to obtain a formed part. The protective atmosphere is argon, the oxygen content in the forming chamber is 100ppm, and the selective laser melting process parameters are: laser power of 320W, scanning speed of 1200mm / s, spot diameter of 70±10μm, powder layer thickness of 50μm, and scanning interval of 120μm. Multi-stage heat treatment: The obtained forming parts are subjected to multi-stage solution treatment and aging treatment in sequence; the process parameters of the multi-stage solution treatment include: holding at 1180℃ for 4 hours, followed by rapid cooling; the process parameters of the aging treatment include: holding at 750℃ for 16 hours, followed by rapid cooling, to manufacture metal products. Preferably, the furnace is kept at 1150℃ for 4 hours, followed by rapid cooling, preferably water cooling, with a cooling rate of ≥100℃ / s, a water temperature requirement of (room temperature water), and a transfer time of ≤15 seconds (from the furnace to the cooling medium). Preferably, the temperature is maintained at 750°C for 16 hours, followed by rapid cooling, preferably air cooling, with a cooling rate of 1-10°C / s and a cooling environment of still air.

[0036] The application areas of the metal products include at least one of the following: Aerospace field: Used in the manufacture of key hot-end components such as high-pressure turbine blades, combustion chamber flame tubes, and turbine disks for aero-engines, enabling integrated forming of internal cooling channels for blades; Energy and power sector: Used in high-temperature turbine blades for gas turbines, heating surface components for waste heat boilers, and high-temperature structural components for the primary loop of nuclear reactors; High-end equipment sector: Used in automotive turbocharger rotors, high-temperature furnace rollers in industrial furnaces, and internal components of high-temperature reaction vessels in the chemical industry.

[0037] The performance test results of the metal products in Example 1 are as follows: 1. Excellent basic performance: The density of the formed metal products is 99.98%, with no microcracks; the microstructure consists of fine equiaxed crystals (grain size 10-20μm), with a uniformly dispersed γ' phase (volume fraction 58%, size 210nm), and no obvious agglomeration or coarsening.

[0038] 2. Improved mechanical properties: No hot isostatic pressing treatment required. Tensile strength: 1452 MPa, yield strength: 1079 MPa, elongation: 12.6%. Tensile strength at 800℃: 1097 MPa, yield strength: 930 MPa, elongation ≥18.5%; Tensile strength at 927℃: 701 MPa, yield strength ≥520 MPa, elongation ≥11.6%.

[0039] 3. Improved creep resistance: At 750℃ / 650MPa, t≥128.7h, under high temperature of 750℃ and stress of 650MPa, the creep resistance reaches 128.7 hours, demonstrating anti-creep properties; 4. Excellent fatigue resistance: 650℃ / 1150MPa, 2*104cyc, no fracture. It has completed 20,000 cycles under alternating stress of 650℃ and 1150MPa without fracture, indicating that the material has excellent thermal fatigue resistance.

[0040] Performance comparison of metal products in Example 1 and metal products in Comparative Examples 1-3: The performance test data of the ACS850-AM metal product from Example 1 were compared with those of commonly used high-temperature metal products such as GH4099, IN738, and IN939. Samples were prepared using the same additive manufacturing process (SLM) for metal 3D printing, and their performance was tested according to the same standards. The comparison results are shown in Table 1 below. Table 1. Comparison of performance test data of the ACS850-AM metal product in Example 1 and the metal products in Comparative Examples 1-3. As can be seen from Table 1, the tensile strength and yield strength of the metal products of the present invention at both room temperature and high temperature are far superior to those of the metal products of Comparative Examples 2-3, and high strength can be achieved without hot isostatic pressing. The 50%-60% high volume fraction γ' phase strengthening effect is significant, enabling the metal product of Example 1 to reach a tensile strength of 1452 MPa at room temperature, while the tensile strength of traditional materials at room temperature is generally lower than 1300 MPa even after hot isostatic pressing. Although the metal product of Comparative Example 3 has a room temperature tensile strength of about 1460 MPa after hot isostatic pressing, the tensile strength of the metal product of Example 1 at 900℃ is 43.7% higher than that of the metal product of Comparative Example 3, and the tensile strength of the metal product of Example 1 at 927℃ is 37.8% higher than that of the metal product of Comparative Example 2. Moreover, the additive manufacturing process of metal 3D printing (SLM) in Example 1 has no microcracks, and its process performance is significantly better than that of Comparative Examples 2 and 3, which have crack defects.

[0041] like Figure 1 As shown in the equilibrium solidification phase diagram of the alloy product provided in Example 1, the phase diagram shows that the solid-liquid two-phase region is controlled. The metal product provided in Example 1 has a wider solid-liquid coexistence range at 1200-1250℃, which significantly reduces the thermal stress concentration during rapid solidification. In addition, element segregation is suppressed, the uniformity of solute distribution between dendrites is improved, and the tendency of liquefaction cracks caused by local melting point fluctuations is effectively avoided.

[0042] like Figure 2As shown in the figure, the morphology of the γ' precipitate and the density scanning electron microscope (SEM) morphology of the alloy product provided in Example 1 are shown. From the figure, we can see that the metal product provided in Example 1 achieves the refinement of the strengthening phase. The γ' precipitate exhibits a highly cubic and regular arrangement, with an average size controlled in the range of 300-500 nm and a volume fraction of 55%-60% (compared to <45% in traditional alloys). This realizes the dislocation movement hindrance mechanism, and the high-density γ' phase forms a three-dimensional hindrance network, which significantly improves the high-temperature creep resistance.

[0043] like Figure 3 As shown, the solidification cracking index of the alloy product provided in Example 1 is - The phase volume fraction comparison chart (red pentagrams indicate the properties of this alloy) shows that the metal product provided in Example 1 has achieved a significant improvement in solidification crack sensitivity. The solidification cracking index of this alloy, marked by red pentagrams, is about 40% lower than that of the traditional benchmark. The total Al+Ti content control (5.0%-10.0%) and Al / Ti mass ratio optimization (0.75-2.0) effectively suppress the formation of γ / γ' eutectic liquid film, while achieving grain boundary engineering optimization. By reducing the precipitation of brittle phases at grain boundaries in the final solidification stage, the integrity of the additive manufacturing process is improved.

[0044] It is understood that this invention has been described through some embodiments, and those skilled in the art will recognize that various changes or equivalent substitutions can be made to these features and embodiments without departing from the spirit and scope of this invention. Furthermore, under the teachings of this invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of this invention. Therefore, this invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are protected by this invention. Furthermore, under the teachings of this invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of this invention. Therefore, this invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of this invention.

Claims

1. A high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, characterized in that, Including: Cr: 8.0%-12.5%, Co: 12.0%-16.5%, W: 2.0%-4.0%, Mo: 3.0%-6.0%, Al: 3.0%-6.0%, Ti: 2.0%-4.0%, Nb: 2.0%-4.5%, Hf: 0.05%-2.0%, C: 0.05%-0.10%, B: 0.005%-0.015%, Fe: 0.1% -1.0%, V: 0.2%-1.0%, Sc: ≤0.005%, La: ≤0.05%, Mg: ≤0.05%, Ce: ≤0.02%, Re: ≤3.0%, Ru: ≤3.0%, Ta: ≤5.0%, S: ≤0.01%, P: ≤0.015%, Si: ≤0.2%, Mn: ≤0.40%, Pb: ≤0.1%; balance is Ni and unavoidable impurities.

2. The high damage tolerance and high fatigue resistance nickel-based superalloy according to claim 1, characterized in that, The total content of Al and Ti elements is 5.0%-10.0%, and the weight ratio of Al to Ti elements is (0.75-2.0):

1.

3. The high damage tolerance and high fatigue resistance nickel-based superalloy according to claim 1, characterized in that, The alloy contains ≥50% γ' strengthening phase by volume.

4. A method for manufacturing a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy, characterized in that, Manufacturing a high-damage-tolerant, high-fatigue-resistance nickel-based superalloy as described in any one of claims 1-3 includes the step of preparing alloy powder using a rotating electrode process, the process comprising: Provide alloy electrode rods that meet chemical composition requirements; In a protective atmosphere and vacuum environment, the electrode rod is rotated at high speed and its end is heated to a molten state to form a liquid film; The liquid film is broken up by the action of centrifugal force and the pressure of a protective atmosphere to form metal droplets, which then solidify to form alloy powder. Collect alloy powder of the desired particle size.

5. The method for manufacturing a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy according to claim 4, characterized in that, The chemical composition of the alloy electrode rod includes: elemental metals with a purity of ≥99.9%.

6. The method for manufacturing a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy according to claim 4, characterized in that, The chemical composition of the alloy electrode rod includes Al and Ti elements. When preparing the alloy electrode rod, the Al and Ti elements are added in the form of Al-Ni and Ti-Ni master alloys.

7. The method for manufacturing a high-damage-tolerance, high-fatigue-resistance nickel-based superalloy according to claim 4, characterized in that, The electrode rod rotates at a speed ≥15000 r / min to generate centrifugal force; the pressure of the protective atmosphere is 0.35-0.55 MPa; and the vacuum degree of the vacuum environment is ≤1×10⁻⁶. -3 Pa.

8. The method for manufacturing high-damage-tolerance, high-fatigue-resistance nickel-based superalloy parts according to claim 4, characterized in that, Prior to the rotating electrode process, the alloy electrode rod is prepared by vacuum melting, including the following steps: Vacuum up to ≤5×10 -3 Pa, under a protective gas atmosphere, is heated to 1500-1700℃ and held for 25-35 minutes, during which time it is stirred until the composition is uniform to obtain molten metal; Molten metal is poured into a mold to form a casting; After cooling to room temperature, the casting is machined to remove the oxide layer on its surface, so that the surface roughness Ra≤1.6μm.

9. An alloy product, characterized in that, Made from high-damage-tolerant, high-fatigue-resistant nickel-based superalloys according to any one of claims 1-3 or alloy powders manufactured by the method described in any one of claims 4-8.

10. An application of the alloy article according to claim 9, wherein the high damage tolerance, high fatigue resistance nickel-based superalloy or the alloy powder is formed into a metal article by additive manufacturing process metal 3D printing, and the application fields of the metal article include at least one of the following: Aerospace field: Used in the manufacture of key hot-end components such as high-pressure turbine blades, combustion chamber flame tubes, and turbine disks for aero-engines, enabling integrated forming of internal cooling channels for blades; Energy and power sector: Used in high-temperature turbine blades for gas turbines, heating surface components for waste heat boilers, and high-temperature structural components for the primary loop of nuclear reactors; High-end equipment sector: Used in automotive turbocharger rotors, high-temperature furnace rollers for industrial furnaces, and internal components of high-temperature reaction vessels in the chemical industry.